Involvement of the blaCTX-M-3 gene in emergence of a peculiar resistance phenotype in Klebsiella pneumoniae - Li, Peishan; Yan, Leping; Song, Jingjie; Lin, Chengfeng; Zeng, Fangyin; Zeng, Shihan (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThis study aimed to investigate the mechanism underlying a peculiar resistance phenotype in Klebsiella pneumoniae, characterized by reduced susceptibility to cefepime compared to ceftazidime.MethodsAntimicrobial susceptibility testing, plasmid conjugation experiments, whole-genome sequencing, and bioinformatic analyses were employed to characterize the resistance phenotype and identify genetic determinants.ResultsA total of 20 K. pneumoniae strains exhibiting peculiar resistance phenotypes were collected and analyzed. Ten distinct sequence types (STs) were identified, including ST25 (4/20), ST967 (3/20), ST65 (2/20), ST133 (2/20), ST48 (2/20), ST353 (1/20), ST628 (1/20), ST753 (1/20), ST792 (1/20), and ST254 (1/20). All strains were resistant to FEP (MIC50 = 128 µg/mL) but not to CAZ (MIC50 = 8 µg/mL). This resistance was primarily attributed to the presence of the blaCTX-M-3 (14/20) and blaOXA-10 (3/20). Conjugation experiments demonstrated that 5 out of 14 blaCTX-M-3-positive K. pneumoniae strains successfully acquired transconjugants, which exhibited the same peculiar resistance phenotype. PCR analysis confirmed that the conjugates contained the IncFII plasmid. To further elucidate the genetic basis of the resistance phenotype, whole-genome long-read sequencing was performed on three blaCTX-M-3-positive K. pneumoniae strains. The sequencing results confirmed that blaCTX-M-3 was located on the IncFII plasmid, and analysis of its genetic environment revealed a frequent association with mobile genetic elements such as IS26, ISEcp1, and Tn3.DiscussionThe primary driver of this phenotype in K. pneumoniae is the presence of the IncFII plasmid carrying blaCTX-M-3, which contrasts with the resistance mechanisms often reported in Pseudomonas aeruginosa exhibiting similar phenotypes. This study emphasizes the critical role of plasmid-mediated resistance in the spread of multidrug resistance in K. pneumoniae and provides insights into strategies for combating resistance in these pathogens.